Turkish intervention in Iraq 1925- 1958 - Salomi, Fatma Hussein (Al-Adab Journal, 2022)
My research which is under the title " Turkish interference in Iraq – 1925 – 2015 " summarized the real beginnings for this interference is started from Mosel problem on 25 July1925 till the outbreak of 14 July revolution 1958. This research shows different stages for this interference through topics and several demands according to the importance of the first stage and claim in Mosel and trends of Turkish authorities in this aspect.Then took new stages from 1930 – 1940 – 1950 with all events and developments within this period, such as " Saadabad Convention and Baghdad Pact " and their influence upon the relation of Iraq with its neighbor countries, besides the research deals with water crisis which was one of the important different matters along with the Turk community which was regarded by Turkish authorities the most important issue regarding it.This study aimed at explaining the reasons behind this interference and the most important issues concerning the relations between two countries which continued for a long time. Finally, the research presents the most important conclusions which perceived from the implications of this interference which goes back to long years especially since the first world war and events and developments after.Despite the demarcation of the boundaries between the two countries, but still the differences are existed in many cases. The most difficult difference is the water crisis which influenced upon the Iraqi economy such as electricity, agriculture and other sectors till nowadays.